Effect of host diets on host preference and host suitability in Telenomus parasitoid (Hymenoptera: Scelionidae) - . Husni; . Jauharlina; . Karmisah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Telenomus sp. is one of the most important biological control agents for several Hemipterous and Lepidopterous  insects.  This study was performed to determine the effect of host diets on host preference and host suitability in Telenomus parasitoid.    In this research, the hosts (Nezara viridula) was reared on the different diets, i.e. Vigna sinensis, Phaseolus vulgaris, and Indigofera suffruticosa.  The result of this experiment showed that the parasitization level of Telenomus sp was not affected by host diets.  However, host diets affected on the percentage of the parasitoid offspring. The percentage offspring was 96%, 81% and 44% from host fed on I. suffruticosa, V. sinensis,and P. vulgaris, respectively. The offspring for all of treatments was biased to female (more than 70%), however it was not affected by host diets. The developmental time for immature stage of Telenomus was also affected by host diets, it was 12, 13 dan 14 days from host fed on I. suffruticosa, V. sinensis,and P. vulgaris, respectively.  These results indicated that I. suffruticosa more suitable host diet for the development of  Telenomus progeny, which may due to more riches nutrients contain in this plant than the other plants.